A scientific overview of the impact of COVID-19 pandemic on sports affairs: A systematic review - Sameer M. Sayyd; Zainal Abidin Zainuddin; Prodhan M. Seraj (Physical Education of Students)
Background and Study Aim. COVID-19 pandemic has impacted all spheres of human life. This study presents the impact of the COVID-19 pandemic on sports activities and the life of sportsmen. It is analysed the inter-connected themes for identifying research trends and motifs from the published studies between March 2020 to March 2021.